{(x-1)²+y² = 4
{y = -1
x²-2x+1+(-1²)=4
x²-2x+1+1=4
x²-2x+2-4=0
x²-2x - 2 = 0
Δ=4-4*1*(-2) = 4+8 = 12
√Δ=√12=2√3
x1=2-2√3/2 = 2(1-√3)/2=1-√3
x2=1+√3
punkty:
p1=(1-√3 , -1)
p2=(1+√3 , - 1)
odp C
" Life is not a problem to be solved but a reality to be experienced! "
© Copyright 2013 - 2025 KUDO.TIPS - All rights reserved.
{(x-1)²+y² = 4
{y = -1
x²-2x+1+(-1²)=4
x²-2x+1+1=4
x²-2x+2-4=0
x²-2x - 2 = 0
Δ=4-4*1*(-2) = 4+8 = 12
√Δ=√12=2√3
x1=2-2√3/2 = 2(1-√3)/2=1-√3
x2=1+√3
punkty:
p1=(1-√3 , -1)
p2=(1+√3 , - 1)
odp C